Design of a Web-Based Medical Equipment Monitoring Information System at Bhakti Yudha Hospital - Evy Nurmiati; Ahmad Khahfi; Musthafa Kamil (Fakultas Teknik Universitas Lambung Mangkurat, 2025)
Effective inventory management is a critical component for ensuring smooth operational continuity, especially in a healthcare setting where timely access to supplies directly impacts patient care. At Bhakti Yudha Hospital, this vital process is hampered by its reliance on manual, spreadsheet-based tracking. This traditional approach is highly susceptible to human error, resulting in significant data inaccuracies and a critical lack of real-time stock visibility, which can ultimately compromise service delivery. To overcome these challenges, a web-based inventory monitoring information system was developed using the Rapid Application Development (RAD) methodology, chosen for its rapid and iterative prototyping capabilities. Modeled with UML diagrams, the system is designed to automate data entry, enhance accuracy, and provide transparent, role-based stock information for both administrators and general users. Key features include an analytical dashboard for strategic oversight, automated low-stock notifications to prevent shortages, and versatile PDF report generation for documentation. Comprehensive black-box testing has confirmed that all core functionalities perform as expected, meeting the initial requirements. This positions the system as an effective solution to significantly optimize the reliability and efficiency of the inventory management process at Bhakti Yudha Hospital.